The Influence of Audit Opinion, Internal Control and External Pressure on Financial Statement Fraud in the Pharmaceutical Sector: An Empirical Study 2019-2023 - Refi Mariska Fitriani; Teguh Budi Raharjo; Abdulloh Mubarok (Jurnal Akuntansi, 2025)
This research seeks to examine the effect of audit opinions, internal control systems, and external pressure on the occurrence of financial statement fraud in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 to 2023. This study applied a quantitative research approach, with a population consisting of 36 pharmaceutical companies. The sample was determined using purposive sampling, based on predetermined criteria, resulting in 15 companies eligible for analysis. The Beneish M-Score model was utilized to assess financial statement fraud. Meanwhile, the audit opinion variable was measured using a dummy variable, internal control was evaluated using the Internal Control Disclosure Index (ICDI), and external pressure was represented by the leverage ratio. The results indicate that internal control has a significant negative relationship with financial statement fraud, whereas external pressure shows a significant positive influence. In contrast, audit opinions do not have a statistically significant impact, suggesting that audit opinions alone may not be sufficient indicators for identifying fraud in pharmaceutical sector companies